ANALISIS KESULITAN MENYIMAK SISWA KELAS III DENGAN PENGGUNAAN MEDIA PEMBELAJARAN AUDIO VISUAL - Putri, Disa Cahaya; Latifah, Nur; Amaliyah, Aam (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Difficulty in listening is a difficulty in understanding what they are listening to and this difficulty in listening can be an obstacle during learning in class, because students can miscapture information or perceptions. This study aims to find out the difficulties of listening experienced by students using audio visual learning media. The research method used is qualitative descriptive. The subjects studied were grade III students of SDN Tanah Tinggi 7 Tangerang. The data collection technique uses test sheets, observation sheets, and interview sheets. The results showed that the causes of students' difficulty listening were students feeling bored, having difficulty concentrating, experiencing visual impairment problems, lack of understanding of listening vocabulary, students being noisy and unsettled when approaching the time to go home, lack of interest in fairy tales, dark room conditions and class hours that started too early. This is based on the internal factors of the student, namely from within the student himself and external factors, namely from the physical and social environment around the student.